Sexual and contraceptives attitudes, the locus of health control and self-esteem among higher education students - José Manuel da Silva Vilelas Janeiro; Isabel Maria Salvado de Oliveira; Maria Helena Guerra Rodrigues; Maria de Jesus Maceiras; Graça Maria Moraes Rocha (Universidade de Fortaleza, 2014)
Objective: To analyze the relationship between sexual and contraceptive attitudes, the locus of health control and self-esteem among students of a private institution of higher education. Methods: Descriptive and correlational study with a quantitative approach, performed in a higher education school in Lisbon, with 152 students, from the 1st to the 4th year of undergraduate courses in Nursing, Physiotherapy, Cardiopneumology and Radiology. As research instrument, it was used a questionnaire with rating scales on 'sexual attitudes', 'contraception attitudes', 'locus of health control' and 'self-esteem'. The data obtained was analyzed using descriptive and inferential statistics. Results: The majority of students (90.7%) have already had sexual intercourse. Sexual attitudes were influenced by gender (p=0.0035), but not by the start of sexual activity or by the course's year (p>0.05). Contraceptive attitudes were related to the year that students attended (p=0.031) and to gender (p=0.029). The external locus of control, on average, was higher among girls (29.2) than boys (30.1). The self-esteem increased with the student's age (p=0.003). Conclusion: Investment in the area of sexual education is needed in the undergraduate programs, since the young people live their days in the school setting, spending little time with their families. The university should assume a special position in the development of the concept of sexuality based on the holistic perspective of the human being, promoting sexual education as essential in the construction of human identity and fundamental for health promotion doi: http://dx.doi.org/10.5020/18061230.2013.p505